2020
DOI: 10.3390/ma13030731
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Optimization of a K0.5Na0.5NbO3-Based Material for Environmentally-Friendly Magnetoelectric Composites

Abstract: Li- and Ta-modified K 0.5 Na 0.5 NbO 3 compounds are among the most promising lead-free ferroelectrics for high-sensitivity piezoelectric ceramic materials, and are potentially capable of replacing Pb(Zr,Ti)O 3 . They are also being investigated as piezoelectric components in environmentally friendly magnetoelectric composites. However, most suitable modifications for this application have not been identified. We report here a simulation study of how the magnetoelectric voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The (1.32 Å) that are present in the A-site, as shown in the ABO3 model [5,20,[22][23][24]. The results agreed well with previously reported results Jiang et al…”
Section: Resultssupporting
confidence: 92%
“…The (1.32 Å) that are present in the A-site, as shown in the ABO3 model [5,20,[22][23][24]. The results agreed well with previously reported results Jiang et al…”
Section: Resultssupporting
confidence: 92%
“…For example, the study of the materials referred to as multiferroics, which combines at least two ferroic orders (ferroelectric, ferromagnetic, or ferroelastic) [1,4,6] has taken great interest because in some of these MF materials, the magnetization can be controlled by an applied electric field, and vice versa, the electric polarization can be controlled by an applied magnetic field. This phenomenon, called magnetoelectric effect (ME) [7,8], is several times greater in the composite MF that in intrinsic MF [9,10]. It is in this sense that the MF bilayer compounds have recently gained great interest.…”
Section: Introductionmentioning
confidence: 99%
“…3 So far, there were only limited numbers of studies on the CFO−KNN particulate composites, although pure or doped KNN and CFO have each been used frequently for making ME composites with other counterparts. 3,6,[11][12][13][14][15] Recently, computer simulation revealed that the composites made of KNN-based ferroelectrics and CFO-based ferrimagnets may potentially have high ME coefficients. 15…”
Section: Introductionmentioning
confidence: 99%
“…3,6,[11][12][13][14][15] Recently, computer simulation revealed that the composites made of KNN-based ferroelectrics and CFO-based ferrimagnets may potentially have high ME coefficients. 15…”
Section: Introductionmentioning
confidence: 99%